Randomized Double-Blind Trial of the Effects of Humidified Compared with Nonhumidified Low Flow Oxygen Therapy on the Symptoms of Patients. Issue 2 (3rd April 1997) - Andres, Darcy; Thurston, Norma; Brant, Rollin; Flemons, Ward; Fofonoff, Doreen; Ruttimann, Ardis; Sveinson, Sandra; Neil, Carol
Abstract : OBJECTIVE: To determine the effects of humidified versus nonhumidified low flow oxygen therapy on the subjective symptoms of patients. METHODS: Randomized double-blind clinical trial conducted in a tertiary care university teaching hospital. The sample included medical and surgical in-patients receiving oxygen therapy who met criteria including medical stability, no overt cognitive impairment, English comprehension, voluntary participation and attending physician agreement. Humidified subjects numbered 96 and nonhumidified subjects were 95. The intervention was humidified or nonhumidified oxygen administration using two flowmeters covered by an opaque bag. Patients receiving oxygen therapy longer than three days (first period) were crossed to the alternate treatment (second period) and followed for three more days. RESULTS: Mean symptom scores for nasal dryness were low (mild) for both groups; however, humidification group scores were significantly lower (P=0.018) in the first period than the nonhumidification scores. A corresponding increase in the incidence of nosebleeds was not statistically significant between groups nor were there statistically significant differences between groups for other symptoms/problems. The prevailing trend was decreased incidence of dry mouth, dry throat, headache and chest discomfort during the study. CONCLUSIONS: Although this sample was large enough to expose statistically significant group differences in nasal dryness, the difference was not judged to be clinically significant. The predominant trend was a decrease in symptom scores over time with either treatment. In this group of patients, humidified oxygen does not appear to alleviate subjective symptoms.